CHANTER Syndrome and mesenteric ischemia presenting concurrently, a case report and literature review - Cagri Yurtsever, MD; Jessica Harris, MD; Alex Breeser, MD; Sudha Ramachandran, MD; Leszek Pisinski, MD (Radiology Case Reports, 2023)
We present a case of a 70-year-old male who was brought to the hospital with altered mental status and was found to have 2 serious complications of cocaine use which are Cerebellar Hippocampal and Basal Nuclei Transient Edema with Restricted diffusion (CHANTER) syndrome and mesenteric ischemia. CHANTER syndrome is a recently described constellation of radiologic and clinical findings and has a strong association with opiates, and/or other drugs of abuse, including cocaine. Even though CHANTER has many similarities with other ischemic, anoxic, and/or toxic injuries related to substance abuse such as clinical presentation and restricted diffusion on magnetic resonance imaging (MRI); the typical distribution of affected regions in the brain is helpful in differentiating from other injuries. With this study, we aim to emphasize the clues that separate CHANTER syndrome from other acute neurologic problems in the setting of substance use. Our case also suggests that the obstructive hydrocephalus, a known possible complication of CHANTER, is likely seen in the cases with severe and central cerebellar involvement. Additionally, it is not common to see complications in 2 different systems concurrently and a multisystemic approach is crucial to a patient with cocaine use to prevent missed life-threatening consequences throughout the various body systems.